2015
DOI: 10.1200/jco.2015.60.9818
|View full text |Cite
|
Sign up to set email alerts
|

Solid Predominant Histologic Subtype in Resected Stage I Lung Adenocarcinoma Is an Independent Predictor of Early, Extrathoracic, Multisite Recurrence and of Poor Postrecurrence Survival

Abstract: A B S T R A C T PurposeTo examine the significance of the proposed International Association for the Study of Lung Cancer, American Thoracic Society, and European Respiratory Society (IASLC/ATS/ERS) histologic subtypes of lung adenocarcinoma for patterns of recurrence and, among patients who recur following resection of stage I lung adenocarcinoma, for postrecurrence survival (PRS). Patients and MethodsWe reviewed patients with stage I lung adenocarcinoma who had undergone complete surgical resection from 1999… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
167
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 195 publications
(173 citation statements)
references
References 41 publications
5
167
1
Order By: Relevance
“…In patients with the SOL predominant subtype, who we reported have early, extrathoracic, and multisite recurrences and poor postrecurrence survival [7], 17% of patients (25/147) had low mPS, compared with 83% with high mPS. There was also strong evidence of an increasing proportion of high mPS with increasing percentage of SOL component, in all patient cohorts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with the SOL predominant subtype, who we reported have early, extrathoracic, and multisite recurrences and poor postrecurrence survival [7], 17% of patients (25/147) had low mPS, compared with 83% with high mPS. There was also strong evidence of an increasing proportion of high mPS with increasing percentage of SOL component, in all patient cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…The use of this well-annotated, previously reported cohort allowed us to assess the prognostic ability of all known clinical, surgical, pathological, histological, and molecular features indicative of aggressiveness—which included lymphatic and vascular invasion [4], type of surgical procedure [7, 19], histological subtypes (defined in the IASLC/ATS/ERS classification) [3, 7, 19], and EGFR and KRAS mutation status [20]. This expansive analysis, inclusive of all known high-risk factors, demonstrated that CCP score and mPS are independent prognostic markers for patients with stage I lung ADC.…”
Section: Introductionmentioning
confidence: 99%
“…One of the key goals of the GTx surgery program is to fund and support research for early tumor detection, when tumors are at their smallest and most treatable stages (14). Innovations within the GTx Lab led to the development of a transportable, intra-operative CBCT that has been established in prospective clinical trials for head and neck surgery in our institution (15).…”
Section: (Ii) Cone-beam Ct Guided Microcoil Localization Of Pulmonarymentioning
confidence: 99%
“…Furthermore, as these tumors tend to be EGFR negative and KRAS positive, they are not amenable to molecular targeting. For this cohort of patients, adjuvant therapeutic strategies require investigation (41).…”
Section: Issues With Current Histologic Classification Systemmentioning
confidence: 99%